(untitled) (Global Journal of Medical Research, 2018)
One of the most common yet mis and poorly understood topic is the ageing process and how it affects the body. Aging is a complex phenomenon that emerges in the coming years. Skin aging can be classified as intrinsic aging and extrinsic aging (photoaging). The skin changes over time due to a decrease in hormone levels, chronic sun exposure, chronic inflammation and many other reasons. It occurs at the microscopic level with physiological, histological and metabolic changes, at macroscopic level with wrinkles, dryness, loss of elasticity and stain formation. Delaying skin aging and alleviating the signs of aging with cosmetic products is one of the most important tasks of cosmetic science. The use of topically applied cosmeceuticals containing ingredients that affect deep biological functions has increased significantly in recent years. Anti aging cosmetic products used in facial care should be scientifically proven products whose efficacy and reliability are intended to show anti-aging effects using different biologically active ingredients. It is the intention of this article to review which biomolecules cause aging, why they do it, and which herbs can prevent unwanted problems caused by aging.